Microstructure and mechanical properties of composites obtained by spark plasma sintering of Al–Fe66Cr10Nb5B19 metallic glass powder mixtures - Dudina, Dina V.; Bokhonov, Boris B.; Batraev, Igor S.; Kvashnin, Vyacheslav I.; Legan, Mikhail A.; Novoselov, Aleksey N.; Anisimov, Alexander G.; Esikov, Maksim A.; Ukhina, Arina V.; Matvienko, Alexander A.; Georgarakis, Konstantinos; Koga, Guilherme Yuuki; et al. (MDPI, 2021)
At present, metallic glasses are evaluated as alternative reinforcements for aluminum matrix composites. These composites are produced by powder metallurgy via consolidation of metallic glass-aluminum powder mixtures. In most studies, the goal has been to preserve the glassy state of the reinforcement during consolidation. However, it is also of interest to track the structure evolution of these composites when partial interaction between the matrix and the metallic glass is allowed during sintering of the mixtures. The present work was aimed to study the microstructure and mechanical properties of composites obtained by spark plasma sintering (SPS) of Al-20 vol.% Fe66Cr10Nb5B19 metallic glass mixtures and compare the materials, in which no significant interaction between the matrix and the Fe-based alloy occurred, with those featuring reaction product layers of different thicknesses. Composite materials were consolidated by SPS at 540 and 570 °C. The microstructure and mechanical properties of composites obtained by SPS and SPS followed by forging, composites with layers of interfacial reaction products of different thicknesses, and metallic glass-free sintered aluminum were comparatively analyzed to conclude on the influence of the microstructural features of the composites on their strength.
Keywords: mechanical properties; reinforcement; interfacial reaction; metal matrix composite; metallic glass